Percutaneous Endovascular Reconstruction With Bare Stent Implantation for Isolated Superior Mesenteric Artery Dissection. (July 2014) - Lü, Peng-Hua; Zhang, Xi-Cheng; Wang, Li-Fu; Shi, Hai-Bin
Background: Spontaneous isolated superior mesenteric artery dissection (ISMAD) is exceedingly rare. The therapeutic options range from observation to medical treatment to surgery or endovascular repair. We present our experience of the clinical management of ISMADs. Methods: Sixteen patients with ISMAD from January 2008 to July 2012 were retrospectively analyzed. The decision to intervene was based on anatomic suitability, patient comorbidities, and symptoms. Percutaneous endovascular reconstruction with bare stents was carried out in 7 patients in this study, for patients with persistent abdominal pain despite conservative treatment or signs of bowel ischemia. The patients were kept on antiplatelet therapy from 6 to 10 months postoperatively. Results: All attempted bare stent placements were successfully accomplished without any treatment-related complication. Of the 7 patients with ISMADs, 4 were treated by single stents, 2 by double overlapping stents, and 1 by triple overlapping stents. The abdominal pain alleviated after procedure and disappeared gradually within 3 days. None of the patients had ISMAD symptoms during follow-up (median, 21.7 months; range, 11-32 months). Follow-up computed tomography (CT) and CT angiography revealed patent stent and patent superior mesenteric artery (SMA) branches with complete obliteration of the dissection. Conclusion: Isolated SMA dissection may be managed successfully in a variety of ways based on the clinical symptoms. In this small series, percutaneous endovascular reconstruction with bare stent implantation is a feasible treatment choice with a high success rate and good clinical outcome.